The Decoloniality of being PoliticalStudies/Science: Legitimising a(nother)way of being - Dube, Siphiwe (Critical Studies in Teaching and Learning, 2023)
In contributing further to the general debate on decolonising Higher Education in South Africa, this article grapples with the question of being for Political Studies/Science. Specifically, the article engages with the question of how might departments of Political Studies/Science begin to imagine and engage the kind of complex decolonised curriculum that pays attention to the relevant structural and sociocultural contexts of South Africa without resorting merely to the additive approach or nominalist model of curriculum transformation as sufficient .In response, the article argues that the notion of being (Barnett,2009) for our curriculum transformation as Political Science/Studies should be of central concern in our decolonisation process. In developing this argument, the article puts forth a theoretical model drawn from an interdisciplinary understanding of what constitutes transformative/decolonised disciplinary legitimation codes(being decolonised),that should be intentionally brought into Political Science/Studies through the language of decolonisation